On being reviewed: from ghosts that haunt in isolation toward connection and unexpected agency. Issue 5 (29th July 2021) - Badenhorst, Cecile; Pickett, Sarah; Arnold, Christine; Lewis, Leah; Vaandering, Dorothy; McLeod, Heather; Buley, Jan; Goodnough, Karen; Maich, Kimberly; Penney, Sharon; Young, Gabrielle
ABSTRACT: Our group of early- and mid-career women faculty members in a mid-sized Canadian university examined the peer review process and our experiences of being reviewed. Using post-structural feminist literature, we theorised how subjectivities are shaped by the pressures of neoliberal incursions into university work. The impact of peer review can be severe and feel highly personal. The peer review system contains assumptions that create conditions for misuse: that reviewers have expertise and that notions of quality scholarly work are shared; that they will be supportive and intellectually ethical; and that they will encourage innovation. We engaged with what it feels like to be reviewed through using collaborative autoethnography as a methodology, and narrative and poetic inquiry as data as well as methods of analysis. We found that how a writer received a review depended on the amount of respect and collegiality in the reviewer's language. Uninformed critical review comments appeared to be particularly damaging. We also found the obscure nature of the process meant that misunderstandings characterised our experiences. Many of us suffered feelings of powerlessness, a homogenisation of writing style, and a decrease in creativity. However, we also found solace and agency in sharing our stories. We shared our experiences within a relational holding space drawing on an ethic of care where well-being flourished, and in which there was an equality of respect, dignity, and mutual concern. We argue this perspective has potential to be applied more broadly to review processes.